2018
DOI: 10.1186/s12872-018-0873-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between increased serum alkaline phosphatase and the coronary slow flow phenomenon

Abstract: BackgroundDespite marked advances in our understanding of the pathophysiology of the coronary slow flow phenomenon (CSFP), the exact mechanism remains unclear. Previous studies have suggested that CSFP might be associated with generalized atherosclerosis, endothelial dysfunction, and low-grade chronic inflammation. High serum alkaline phosphatase (ALP) levels are associated with vascular calcification, atherosclerotic disease, and an increased risk of cardiovascular events. However, the relationship between AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Tambe et al described it for the first time in 1972. CSFP manifests clinically similarly to coronary atherosclerotic heart disease [8][9][10]. In agreement with our study, Mahfouz et al [11] conducted a case control study, taking patients admitted to cardiac catheterization for suspected coronary artery disease.…”
Section: Discussionsupporting
confidence: 89%
“…Tambe et al described it for the first time in 1972. CSFP manifests clinically similarly to coronary atherosclerotic heart disease [8][9][10]. In agreement with our study, Mahfouz et al [11] conducted a case control study, taking patients admitted to cardiac catheterization for suspected coronary artery disease.…”
Section: Discussionsupporting
confidence: 89%
“…Experimental and clinical studies link ALP to increased vascular calcification and inflammation. Epidemiological studies have demonstrated correlations between serum ALP activity and the incidence of death [2,3] or major adverse cardiovascular events (MACE) [4,5], myocardial infarction [6], stroke [7], cerebral small vessel disease [8], re-stenosis after coronary revascularization [9], coronary slow flow phenomenon [10], and peripheral arterial disease [11]. Circulating ALP is associated with coronary calcification [12,13] and ALP activity is implicated in calcification of vascular smooth muscle cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…It seems that patients with CSFP may have an underlying inflammatory state and endothelial dysfunction [ 31 , 38 ]. A study by Narimani et al on CSFP patients found high LDL and low HDL levels in these patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%